Biovalorisation of brewer's spent grain (BSG) and sensory evaluation of BSG bread - Goh, Luo Lin (Nanyang Technological University, 2021)
Brewer’s spent grain (BSG) is the largest by-product of beer production, generating over an approximate 38 billion kg annually. While the majority of BSG gets repurposed as animal feed, its usage unfortunately remains very limited. Due to the impressive nutritional profile of BSG, many studies have investigated its incorporation in food products. However, its substitution at high levels tend to bring about undesirable sensory changes. This paper looks at solid-state fermentation as a tool to enhance the nutritional profile of BSG. The consumer acceptance of fermented BSG- fortified bread was investigated, to understand the market value for fermented BSG food products compared to its unfermented counterpart. Of the 8 koji starters studied, M-1 (Aspergillus oryzae) brought about the greatest nutritional profile enhancement in terms of total phenolic content and crude protein content, with an optimal fermentation time of 4 days. No change in total dietary fibre content was observed after fermentation. From the sensory evaluation, fermented BSG-fortified bread had the best nutritional profile while having the poorest consumer acceptance. Despite the fact, this study highlights that fermentation may yet be an important tool in bridging the gap of BSG incorporation in food.